Unravelling Art Practice and Education Entanglements in Academia: An Interview with Marco Buti - Marcelo Schellini (Arte, Individuo y Sociedad)
Marco Buti is a visual artist and academic professor known for his rigorous exploration of various mediums, including printmaking, drawing, and photography. He is also recognized for his contributions to art education and his critical reflections on artistic practice and its teaching in academic settings. Born in Empoli, Italy, in 1953, Buti moved to Brazil in 1962, where his artistic and educational work has played a significant role in the development of the visual arts. He has published several books and exhibited his artwork in numerous solo and group exhibitions internationally. In 1997, he received the Printmaking Prize from the São Paulo Association of Art Critics (APCA), and in 1999, he was awarded the Internazionale di Biella per l'Incisione prize in Biella, Italy. Buti taught printmaking and drawing at the State University of Campinas from 1986 to 1995. Since 1996, he has been a professor in the Department of Visual Arts at the School of Communications and Arts at the University of São Paulo, where he served as department head from 2002 to 2007. This interview was conducted online in December 2024.